Dermatitis herpetiformis bodies and autoantibodies to noncutaneous organs and mitochondria in dermatitis herpetiformis - Ana Maria Abreu Velez; Hong Yi; Julia Griffin Girard; Zhe Jiao; Mauricio Duque Ramírez; Luis F. Arias; Bruce B. Smoller; Samuel C. Dudley Jr; Michael S. Howard (Our Dermatology Online, 2012)
Introduction: The precise nature of the previously described dermatitis herpetiformis bodies remains unknown.Aims: Our study was conducted to investigate the nature of dermatitis herpetiformis bodies in the skin in 7 cases of dermatitis herpetiformis, and to search for the presence of autoantibodies in other organsMethods: We utilized clinical, histopathologic, and immunologic methods to evaluate these patients.Results: Dermatitis herpetiformis bodies were found to be comprised of an amalgamation of immunoglobulins A and M, as well as molecules reactive with antibodies to armadillo repeat gene deleted in velo-cardio-facial syndrome, desmoplakins 1 and 2, and plakophilin 4. In addition, we found immunologic colocalization with selected autoantibodies associated with mitochondria in the skin, heart, kidney, and peripheral nerves. The dermatitis herpetiformis bodies did not demonstrate immunologic colocalization with tissue/epidermal transglutaminase.Conclusion: The complete biochemical nature of dermatitis herpetiformis bodies requires further characterization. Dermatitis herpetiformis bodies in these patients appear to be distinctly different than cytoid bodies. Further studies are required to determine if the antibodies to noncutaneous organs are pathogenic, and/or contribute to systemic morbility in dermatitis herpetiformis patients.